Trends in handwashing behaviours for COVID-19 prevention: Longitudinal evidence from online surveys in 10 sub-Saharan African countries - Bolanle Olapeju; Zoé Mistrale Hendrickson; Joseph G. Rosen; Dominick Shattuck; J. Douglas Storey; Susan Krenn; Marla Shaivitz; Elizabeth Serlemitsos; Tuo-Yen Tseng; Samantha W. Tsang; Rajiv N. Rimal; Stella Babalola (Public Library of Science (PLoS), 2021)
Handwashing is essential for respiratory virus prevention, but uptake of handwashing in the context of the SARS-CoV-2 pandemic remains under-explored. This study examines trends in and determinants of handwashing practices for COVID-19 prevention in 10 countries in West, East, and Southern Africa. Data are derived from an online global Facebook survey assessing COVID-19 knowledge, attitudes, and practices, fielded in July (Round 1) and November 2020 (Round 2). Adults ≥18 years (N = 29,964) were asked if they practiced handwashing with soap and water in the past week to prevent COVID-19. Design-corrected F-statistics compared knowledge and practice of handwashing, at country and regional levels, between survey rounds. A country-level fixed-effects logistic regression model then identified socio-demographic and ideational correlates of handwashing at Round 2. Most participants were >30 years-old, men, post-secondary educated, and urban residents. Between survey rounds, handwashing prevalence declined significantly across regions and in each country, from a 14% decline (Δ84%-70%) in Tanzania to a 3% decline (Δ92%-89%) in South Africa. Handwashing was higher among participants aged >30 years (Adjusted Odds Ratio [aOR] = 1.25, 95% confidence interval [95%CI]: 1.15-1.35) and with post-secondary education (aOR = 1.62, 95%CI: 1.49-1.77) but lower among men (aOR = 0.71, 95%CI: 0.64-0.78). Ideational factors associated with handwashing included perceived effectiveness of handwashing (aOR = 2.17, 95%CI: 2.00-2.36), knowing someone diagnosed with COVID-19 (aOR = 1.28, 95%CI: 1.18-1.40), and perceived importance of personal action for COVID-19 prevention (aOR = 2.93; 95%CI: 2.60-3.31). Adjusting for socio-demographic and ideational factors, country-level marginal probabilities of handwashing ranged from 67% in Tanzania to 91% in South Africa in Round 2. COVID-19 prevention messages should stress the importance of handwashing, coupled with mask use and physical distancing, for mitigating respiratory disease transmission. Behaviour change communications should be sensitive to resource heterogeneities in African countries, which shape opportunities for sustainable handwashing behaviours.